Intercalation of Co-complex into the layered structure of VOPO4.2H2O for the preparation of vanadyl pyrophosphate, (VO)2P2O7 catalyst - Yap, Taufiq Yun Hin; Matali, S.; Hussein, Mohd Zobir (Malaysian Solid State Science and Technology Society, 2009)
Layered vanadyl phosphate dihydrate, VOPO4·2H2O is one of the precursor to vanadyl pyrophosphate (VPO) catalyst which is the sole catalyst used industrially for the partial oxidation of n-butane to maleic anhydride. With a basal spacing of 0.74 nm, layered VOPO4·2H2O was used as the host and Co-complex (Co(acac)2) as a guest The obtained precursor, VOHPO4·0.5H2O was confirmed by XRD and were activated in a reaction flow of n-butane/air mixture (0.75% n-butane/air) to form vanadyl pyrophosphate catalyst ((VO)2P2O7) at 460oC for 18 h. Both catalysts were characterised by using several methods i.e. X-ray Diffraction (XRD), Braunner Emmer Teller (BET) surface area and Temperature Programmed Reduction (TPR), Redox titration and Scanning Electron Microscopy (SEM). Co-complex was succesfully intercalated into the layer and as proven by XRD with a presence of a new peak appeared at 2θ = 6.8º and another new peak was also observed at 2θ = 13.5 º. TPR studies of Co intercalated VPO shows a sharp peak come with larger area (compared to unintercalated catalyst) which correspond to the removal of oxygen species associated to V4+ phase. Another peak at lower temperature which corresponds to the oxygen species released from V5+ phase. An improved of n-butane conversion is expected due to the increment of the active oxygen species (O-) which responsible to the activation of n-butane. Higher amount of oxygen linked to V5+ also will contribute to the activity of the Co-intercalated catalyst.